Gestational Age Dependency of Umbilical Cord Serum IL-6 Levels for Detecting Fetal Inflammation - Iwatani, Sota; Kobayashi, Takao; Matsui, Sachiko; Hirata, Akihiro; Yamamoto, Miwa; Yoshida, Makiko; Yoshimoto, Seiji; Nakao, Hideto (American Journal of Perinatology, 2020)
Objective The fetal inflammatory response syndrome (FIRS) is characterized by elevated concentrations of inflammatory cytokines in fetal blood, with preterm delivery and morbidity. Umbilical cord serum interleukin-6 (UC-s-IL-6) is an ideal marker for detecting FIRS. However, the effect of gestational age (GA) on UC-s-IL-6 levels has not been reported. This study aimed to determine the relationship between GA and UC-s-IL-6 levels, and GA-dependent cutoff values of UC-s-IL-6 levels for detecting fetal inflammation.Study Design UC-s-IL-6 concentrations were measured in 194 newborns (44 extremely preterm newborns (EPNs) at 22–27 weeks' GA, 68 very preterm newborns (VPNs) at 28–31 weeks' GA, and 82 preterm newborns (PNs) at 32–34 weeks' GA). Linear regression analyses were used to correlate GA and UC-s-IL-6 levels. Receiver operating characteristic (ROC) curves analyses were performed for detecting the presence of funisitis, as the histopathological counterpart of FIRS.Results A significant negative correlation between GA and UC-s-IL-6 levels was found in newborns with severe funisitis (rs =  − 0.427, p = 0.004) and those with mild funisitis (rs =  − 0.396, p = 0.025). ROC curve analyses revealed the area under the curve for detecting funisitis were 0.856, 0.837, and 0.622 in EPNs, VPNs, and PNs, respectively. The UC-s-IL-6 cutoff value in EPNs (28.1 pg/mL) exceeded those in VPNs and PNs (3.7 and 3.0 pg/mL, respectively).Conclusion UC-s-IL-6 levels were inversely correlated with GA especially in newborns with funisitis. Such GA dependency of UC-s-IL-6 should be considered for detecting fetal inflammation.Key Points
Keywords: interleukin-6; umbilical cord blood; gestational age; fetal inflammatory response syndrome; funisitis